Risk Factor and Surgical Outcome of Petersen’s Hernia After Gastrectomy in Gastric Cancer - Song Liu (Frontiers Media S.A., 2021)
BackgroundPetersen’s hernia is a life-threatening complication after gastrectomy. This study is dedicated to identify risk factors for Petersen’s hernia and compare clinical outcomes between patients receiving early or delayed surgical interventions.MethodsData from all patients who received gastrectomy due to gastric cancer were collected. Clinical characteristics were compared between Petersen and non-Petersen groups, bowel necrosis and non-necrotic groups. Propensity score matching (PSM) was conducted to generate two comparative groups. Univariate analysis and multivariate logistic regression were performed for risk factor evaluation.ResultsA total of 24 cases of Petersen’s hernia were identified from 1,481 cases of gastrectomy. PSM demonstrated that lower body mass index [BMI; odds ratio (OR) = 0.2, p < 0.01] and distal gastrectomy (OR = 6.2, p = 0.011) were risk factors for Petersen’s hernia. Longer time interval from emergence visit to laparotomy (p = 0.042) and elevated preoperative procalcitonin (p = 0.033) and C-reactive protein (CRP; p = 0.012) were associated with higher risk of bowel necrosis in Petersen’s hernia. Early surgical intervention resulted in less bowel necrosis rate (p = 0.012) and shorter length of necrotic bowel (p = 0.0041).ConclusionsLow BMI and distal gastrectomy are independent risk factor for Petersen’s hernia after gastrectomy. Curtailing observing time and executing prompt surgery are associated with bowel viability and better outcome in patients with Petersen’s hernia.